Tree Health Typology of Homegardens and Dry Fields Along an Altitudinal Gradient in Kulon Progo, Indonesia - S. M. Widyastuti; Indira Riastiwi; Priyono Suryanto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
Homegarden–dry field is one of land management form that maintains biodiversity while at the same time synergize the production and conservation. Changes in market conditions pose a threat for monoculturalism on homegarden and dry field. On the basis of this consideration, it is necessary to do a research on trees health in homegarden and dry field. This study aimed to determine the constituent species in the agroforestry system of Kulon Progo, tree health typology in Kulon Progo, and the type of damages to homegarden and dry field tree species in agroforestry. This research method used inventory of species in the agroforestry system and identification of damage to trees using Forest Health Monitoring (FHM). The result showed that there were three typologies of trees’ health. Those were classified into typology 1, 2 and 3 in Kulon Progo. The types of damage that present at homegarden and dry field in Kulon Progo are the open wound, galls rust, broken branch, leaf spot, excessive branching, gummosis and termite attack.